A multi vector energy analysis for interconnected power and gas systems. (15th April 2017) - Devlin, Joseph; Li, Kang; Higgins, Paraic; Foley, Aoife
Highlights: The first multi vector energy system analysis for Britain and Ireland is performed. Extreme weather driven gas demands were utilised to increase gas system stress. GB gas system is capable of satisfying demand but restricts gas generator ramping. Irish gas system congestion causes a 40% increase in gas generator short run cost. Gas storage in Ireland relieved congestion reduced operational costs by 14%. Abstract: This paper presents the first multi vector energy analysis for the interconnected energy systems of Great Britain (GB) and Ireland. Both systems share a common high penetration of wind power, but significantly different security of supply outlooks. Ireland is heavily dependent on gas imports from GB, giving significance to the interconnected aspect of the methodology in addition to the gas and power interactions analysed. A fully realistic unit commitment and economic dispatch model coupled to an energy flow model of the gas supply network is developed. Extreme weather events driving increased domestic gas demand and low wind power output were utilised to increase gas supply network stress. Decreased wind profiles had a larger impact on system security than high domestic gas demand. However, the GB energy system was resilient during high demand periods but gas network stress limited the ramping capability of localised generating units. Additionally, gas system entry node congestion in the Irish system was shown to deliver a 40% increase in short run costs for generators. Gas storage was shown to reduce the impact of high demand driven congestion delivering a reduction in total generation costs of 14% in the period studied and reducing electricity imports from GB, significantly contributing to security of supply.